Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 3019 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Rourea Aubl.", { "or" : [ "Geometry POLYGON((-22.851562 23.885837,-22.851562 -36.879620,22.5 -36.879620,22.5 23.885837,-22.851562 23.885837))", "Geometry POLYGON((76.113281 24.206889,76.113281 8.928487,111.093749 8.928487,111.093749 24.206889,76.113281 24.206889))", "Geometry POLYGON((112.851562 15.453680,112.851562 1.757536,139.394531 1.757536,139.394531 15.453680,112.851562 15.453680))" ] } ] } The dataset includes 3019 records from 85 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0072305-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences